POTENSI MAKROFAUNA AKUATIK EKOSISTEM HUTAN MANGROVE DI KAWASAN PESISIR DESA KAMPUNG NIPAH SEI NAGALAWAN KECAMATAN PERBAUNGANKABUPATEN SERDANG BEDAGAI - Ummi Febriani Ritonga; Yunasfi Djayus; Indra Lesmana (AQUACOASTMARINE, 2018)
Kampung Nipah Sei Nagalawan Village is a marine biota producer area such as aquatic macrofauna and mangroves. Villagers of Sei Nagalawan generally have livelihoods as fishemen. Their lives depend on seafood obtained through both fishing and cultivation. So the need to increase the potential problems against the biota. However, from excessive community activity on mangroves can damage the ecosystem so that there is a physical decline and water quality degradation of the mangrove ecosystem. This study aims to analyze the level of abundance, biomass, diversity and evenness and to analyze the pattern of the spread of aquatic macrofauna around the mangrove. This research was conducted in March – May 2017. This research was conducted by survey method and sampling was done by purposive sampling method. The results showed that the condition of aquatic macrofauna in the mangrove area of Kampung Nipah Sei Nagalawan was rare and the macro-aquatic macrofauna pattern was very minimal due to the large number of mangrove land that was damaged to reduce the habitat for the biota.Keywords : Mangrove, Aussiatic Macrofauna, Nipah Villege, Sei Nagalawan Village, Serdang bedagai